Sustainability as a fair bequest: an evaluation challenge - Klauer, Bernd; Manstetten, Reiner; Petersen, Thomas (Ecological economics, 2017)
In contrast to conventional approaches the conceptualisation of sustainability as fair bequest makes it possible to consider a finite time horizon. Valuation is necessary to determine whether the bequest package that is passed on from one generation to the next is fair. Acknowledging the merits as well as the limitations of economic price theory, this paper differentiates between three classes of valuables: the essential, the useful and the unique. It is argued that a fair bequest package should contain items from each of the classes. Because the three classes are incommensurable, fairness of the bequest cannot be expressed by a single figure like a non-declining total value of the package. We then discuss which methods are appropriate for describing a bequest package with respect to its fairness.
Available online 9 June 2017
Gesehen am 23.10.2018